Exploring the Positive User Experience Possibilities Based on Product Emotion Theory: A Beverage Unmanned Retail Terminal Case - Cao, Enguo; Duan, Yanjun; Jiang, Jinzhi; Peng, Hui; Hu, Weifeng (Frontiers in Psychology, 2022)
Since the last century, user experience has been regarded as a key concept in the process of product and service design. With the development of positive psychology, the transformation from negative to positive has also taken place in the field of user experience, it emphasizes exploring the positive user experience future possibility, rather than just solving existing problems. Based on the research and analysis of existing literature, this study makes it clear that the positive user experience research should be based on the "positive experience", and arousing positive emotion is conducive to improving the positive user experience. On this basis, the product emotion theory is applied to the analysis process of "positive experience". Through word frequency screening, thematic analysis and correlation calculation, the relationship between product stimulus (object, activity,identity) and user concern (goal, attitude, standard) based on positive "user comments" is constructed, and the positive user experience is understood from multiple levels. Combined with the comment score, the positive user experience interval is divided, in order to clarify the improvement direction. Finally, taking the "Angel Orange" unmanned-retail terminal as an example, this paper makes an empirical analysis. As an exploratory study, it is hoped that this work can provide some insights into the quantitative research process of positive user experience design that evokes positive emotions from user "positive experience" story.